Constitutional frameworks and democratization in Africa since independence - Neirynck, Karim (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
The subject of this thesis is international studies, specifically a study of constitutional frameworks in Africa in the second half of the 20th century, focussing on a statistical correlation between constitutional frameworks, party systems, electoral systems and the Index of Democracy. The struggle to consolidate new democracies - especially those in Eastern Europe, Latin America and Asia - has given rise to a wide-ranging debate about the hard choices concerning democratic political institutions and political markets. According to Stepan and Skach " this literature has produced provocative hypotheses about the effects of institutions on democracy" (Stepan and Skach, 1993 : 1). It forms part of the' new institutionalism I literature in comparative politics that'holds as a premise that political democracy depends not only on economic and social conditions but also on the design of political institutions (Koelble, 1995 : 231-243). " One fundamental political-institutional question that has only received serious scholarly attention concerns the impact of different constitutional frameworks on democratic consolidation. Although the topic has been increasingly debated and discussed, little systematic cross-regional evidence [especially for our field of research: Africa] has been brought to bear on it " (Stepan and Skach, 1993 : 1-2). So far, only the book"on regime transitions in Africa written by Bratton and Van De Walle seeks to fill this empirical gap (Bratton and Van De Walle, 1997, preface xiii). In this thesis, we paid particular attention to the dichotomy between (pure) parliamentarism and (pure) presidentialism. Each type has fundamental characteristics, and for the purposes of classification these characteristics are necessary and sufficient. It was not our purpose to weigh the benefits and drawbacks of parliamentarism and presidentialism. Our intention was to report and analyse different sources of data, and we based our case exclusively on statistic correlatiohs between regime type and the record of democratic success and failure. We collected a data set about constitutional frameworks (matrix1), democracy indices (matrix2), party systems (matrix3) and election systems (matrix4). The basis for matrix 1 was the constitutions of the African countries (over time) and relevant literature. The basis for matrix 2 was the annual Freedom House ratings made by Raymond D. Gastil and others. The basis for matrix 3 and 4 was relevant literature. Once these matrices had been composed, we compared them and calculated statistic correlations. This long-dyration model allowed us to estimate whether African constitutional frameworks, party systems and electoral systems exhibit positive or negative correlation with the index of democracy.
Keywords: Democracy -- Africa; Constitutions -- Africa; Africa -- Politics and government -- 1960-